(Under)Mining local residential property values: A semiparametric spatial quantile autoregression. (4th October 2018) - Malikov, Emir; Sun, Yiguo; Hite, Diane
Summary: Rock mining operations, including limestone and gravel production, have considerable adverse effects on residential quality of life due to elevated noise and dust levels resulting from dynamite blasting and increased truck traffic. This paper provides the first estimates of the effects of rock mining—an environmental disamenity—on local residential property values. We focus on the relationship between a house's price and its distance from a nearby rock mine. Our analysis studies Delaware County, Ohio, which, given its unique features, provides a natural environment for the valuation of property‐value‐suppressing effects of rock mines on nearby houses. We improve upon the conventional approach to evaluating adverse effects of environmental disamenities based on hedonic house price functions. Specifically, in the pursuit of robust estimates, we develop a novel (semiparametric) partially linear spatial quantile autoregressive model which accommodates unspecified nonlinearities, distributional heterogeneity, as well as spatial dependence in the data. We derive the consistency and normality limit results for our estimator as well as propose a consistent model specification test. We find statistically and economically significant property‐value‐suppressing effects of being located near an operational rock mine which gradually decline to insignificant near‐zero values at roughly a 10‐mile distance. Our estimates suggest that, all else equal, a house located a mile closer to a rock mine is priced, on average, at about 2.3–5.1% discount, with more expensive properties being subject to larger markdowns.